Women’s Transition to Entrepreneurs from Professional and Managerial Careers in Organizations - Nindria Untarini; Sayyida Sayyida; Dwiarko Nugroho Seno (Binus Business Review, 2021)
Careers have different dimensions, they can be developed in an organization and in individual way. Organizations no longer have a role in creating careers, but individuals develop careers using the organization as a tool or medium. Changes in the external and internal environment in the organization are the basic conditions why individual career dares to change. The research aimed to explore senior female managers’ phenomenon that left professional and managerial careers in organizations to be entrepreneurs. Structured and in-depth interviews were conducted with 25 female entrepreneurs who had left senior manager positions at the companies. Qualitative research approaches were carried out to explore what motivated female entrepreneurs to make a career transition and how the career transition process was done. Then, the Critical Incident Technique was used to analyze the data to get responses regarding female entrepreneurs’ perceptions of career transitions. From the results, there are four main categories: personal, organizational life, value and integrity, and capital. Then, there are also nine subcategories: independence and individualism, strong encouragement and family support, professional and personal life balance, organizational life, values, integrity, partner ties, mentor ties, and human capital. The personal category causes more women to make a career transition, followed by capital, value and integrity, and organizational life categories.